Efeito da exigência de respostas ecoicas durante o ensino de discriminação auditivo-visual na emergência de tatos em crianças com autismo - Carneiro, Anne Caroline da Costa (Universidade Federal de São Carlos, 2021)
Many studies have been developing procedures to teach verbal repertoires to children diagnosed with Autism Spectrum Disorder (ASD). The purpose of this study was to evaluate the efficacy of a auditory visual discrimination training with and without echoic response requirement in the emergence of tacts in children with autism, and evaluate if the moment in which the response was required (e.g., after the auditory stimulus was presented meanwhile children attempted to the visual stimulus) could lead to the emergence of tact responses. 3 children diagnosed with ASD participated in the study and were exposed to the following experimental conditions: 1) Pretest tact probe, with the purpose of evaluate the participant's entry repertoire and choose the target stimulus, 2) Auditory visual discrimination training with echoic response requirement to one set of stimulus in which the participant was required to emit the echoic response after the auditory stimulus was presented meanwhile children attempted to the visual stimulus, 3) Auditory visual discrimination training without echoic response requirement to another set of stimulus, and, 4) posttest tact probe to evaluate the effects of echoic responses requirement in the emergence of tacts. An alterned treatment design was implemented allowing the evaluation inter and intra participants. The results demonstrates a high level of tact emergence for all participants suggesting that echoic responses requirement in an specific moment in which it is emitted could play an important role in the emergence of tacts in as auditory visual discrimination training procedure.
The effects of echoic response requirement during auditory visual discrimination training on the emergence of tacts in children diagnosed with autism
Keywords: Crianças com autismo; Discriminação auditivo-visual; Ecoico; Nomeação bidirecional; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::APRENDIZAGEM E DESEMPENHO ACADEMICOS